UV-luminous, star-forming hosts of z ∼ 2 reddened quasars in the Dark Energy Survey. Issue 3 (5th January 2018) - Wethers, C F; Banerji, M; Hewett, P C; Lemon, C A; McMahon, R G; Reed, S L; Shen, Y; Abdalla, F B; Benoit-Lévy, A; Brooks, D; Buckley-Geer, E; Capozzi, D; et al.
Abstract: We present the first rest-frame UV population study of 17 heavily reddened, high-luminosity [ E ( B − V )QSO ≳ 0.5; L bol > 10 46 erg s −1 ] broad-line quasars at 1.5 < z < 2.7. We combine the first year of deep, optical, ground-based observations from the Dark Energy Survey (DES) with the near-infrared VISTA Hemisphere Survey and UKIDSS Large Area Survey data, from which the reddened quasars were initially identified. We demonstrate that the significant dust reddening towards the quasar in our sample allows host galaxy emission to be detected at the rest-frame UV wavelengths probed by the DES photometry. By exploiting this reddening effect, we disentangle the quasar emission from that of the host galaxy via spectral energy distribution fitting. We find evidence for a relatively unobscured, star-forming host galaxy in at least 10 quasars, with a further three quasars exhibiting emission consistent with either star formation or scattered light. From the rest-frame UV emission, we derive instantaneous, dust-corrected star formation rates (SFRs) in the range 25 < SFRUV < 365 M⊙ yr −1, with an average SFRUV = 130 ± 95 M⊙ yr −1 . We find a broad correlation between SFRUV and the bolometric quasar luminosity. Overall, our results show evidence for coeval star formation and black hole accretion occurring in luminous, reddened quasars at the peak epoch of galaxy formation.